Global surveillance, prevention and control of chronic respiratory diseases : a comprehensive approach - Bousquet, Jean (WHO GenevaCH, 2007)
Seeks to raise awareness of the huge impact of chronic respiratory diseases worldwide. Highlights the risk factors as well as ways to prevent and treat these diseases.